Dual Political Role of Art: A Critical Discourse Analysis of Faiz Ahmed Faiz’s “National, Art and Culture” - Isma Zaheer; Asma Khan; Fatima Razzaq (University of Chitral Journal of Linguistics and Literature, 2023)
Every culture has its own customs and values so when an artist produces any kind of cultural work, he must be influenced by the norms of society. This study investigates how art explores the “mystical capabilities” or “power” that originates with for. It also discloses how the power of art plays a significant part in creating a multi-cultural society. Gee’s “Seven Building Tasks”, A popular model for showing seven realms of reality, serves as a theoretical foundation for this study. The main points of this model are i. significance, ii. practices (activities), iii. identities, iv. relationships, v. politics (the distribution of social goods), vi. Connections, vii. sign systems and knowledge (Gee, 1999, p.8). The results of this study indicate that art is important to culture, and both are interconnected to each other. This study of art and culture is used to express some moral standards, ethnicity, racial differences as well as religious groups. So, the study recommends that the social groundwork should be created on communal stories, ethics, and principles. There should be an addition of cultural texts to our study to promote art and culture.